1980
DOI: 10.1128/jb.142.2.621-632.1980
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of fatty acid degradation in Escherichia coli: isolation and characterization of strains bearing insertion and temperature-sensitive mutations in gene fadR

Abstract: Transposon TnlO was used to mutagenize the fadR gene in Escherichia coli. Mutants bearing fadR::TnlO insertion mutations were found to (i) utilize the noninducing fatty acid decanoate as sole carbon source, (ii) f8-oxidize fatty acids at constitutive rates, and (iii) contain constitutive levels of the five key ,B-oxidative enzymes. These characteristics were identical to those observed in spontaneous fadR mutants. The constitutive phenotype presented by the fadR: :TnlO mutants was shown to be genetically linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
45
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(51 citation statements)
references
References 23 publications
6
45
0
Order By: Relevance
“…In the course of analyzing the effects of fatty acid composition on the properties of the mitochondrial glycerophosphate dehydrogenase (4) of Neurospora, we noted that both wild-type and Cel-strains possess the ability to grow when long-chain fatty acids are present in the medium as the sole carbon and energy source, as earlier suggested from the fatty acid supplementation of Ace-mutants (11). These observations indicated that Neurospora possesses a a-oxidation pathway with some features similar to those previously described for the fatty acid degradation (FAD) system in Escherichia coli (13,14,16). In this report, we describe the intracellular localization and inducibility of the fatty acid oxidation enzymes acyl coenzyme A (CoA) synthetase (EC 6 Growth of cells aid assay of FAD enzymes.…”
supporting
confidence: 81%
“…In the course of analyzing the effects of fatty acid composition on the properties of the mitochondrial glycerophosphate dehydrogenase (4) of Neurospora, we noted that both wild-type and Cel-strains possess the ability to grow when long-chain fatty acids are present in the medium as the sole carbon and energy source, as earlier suggested from the fatty acid supplementation of Ace-mutants (11). These observations indicated that Neurospora possesses a a-oxidation pathway with some features similar to those previously described for the fatty acid degradation (FAD) system in Escherichia coli (13,14,16). In this report, we describe the intracellular localization and inducibility of the fatty acid oxidation enzymes acyl coenzyme A (CoA) synthetase (EC 6 Growth of cells aid assay of FAD enzymes.…”
supporting
confidence: 81%
“…The fact that MabR is the regulator that fine-tunes expression of the genes encoding the FAS-II and possibly the FAS-I systems would also support the essential role of this protein. Interestingly, the essentiality of mabR for M. smegmatis growth is in sharp contrast to the other FA regulatory proteins characterized in bacteria so far, since all of them have been shown to be non-essential for survival of the corresponding microorganism, including FasR of S. coelicolor (Simons et al, 1980;Schujman et al, 2003;Lu and Rock, 2006;Arabolaza et al, 2010).…”
Section: Discussionmentioning
confidence: 87%
“…The fasR gene has been proposed to be essential in M. tuberculosis based on a combination of high density mutagenesis and deep sequencing analysis (Griffin et al, 2011). Interestingly, most of the fatty acid biosynthesis regulators described so far in bacteria are not essential for survival (Simons et al, 1980;Schujman et al, 2003;Lu and Rock, 2006). The only exception is MabR, a novel regulatory protein involved in mycolic acid biosynthesis regulation in mycobacteria (Salzman et al, 2010).…”
Section: Fasr Is Essential For Mycobacteria Viabilitymentioning
confidence: 99%